Evaluasi CPPB-IRT dan HACCP pada UMKM Olahan Limbah Kulit Ikan Patin - Ruenda, Okti; Marvie, Ilham; Lianti, Lita; Sihombing, Marcell; Irbadh, Muhammad; Sinaga, Febriyanti; Silaban, Martuah (Jurnal Ilmu Pangan dan Hasil Pertanian, 2025)
MSMEs producing catfish skin chips offer economic potential but face limitations in food safety management. This study aimed to evaluate compliance with Good Processed Food Production Practices for Home Industries (CPPB-IRT) and the implementation of the Hazard Analysis and Critical Control Points (HACCP) system at a catfish skin chip MSME in Bandar Lampung. A descriptive quantitative approach was used through observations, interviews, and documentation analysis.